Écriture inclusive, lisibilité textuelle et représentations mentales - Cyril Liénardy; Julia Tibblin; Pascal Gygax; Anne-Catherine Simon (Discours)
Since the fall of 2017, when it was brought to the public debate, gender-inclusive writing has sparked passionate reactions. The debates generated by this linguistic practice are divisive and the discussion on certain aspects, such as the so called midpoint, is paralysed. Many arguments are mobilised by opponents, such as the unreadability of gender-inclusive writing, or the absence of ambiguity in the use of the generic masculine and therefore the uselessness of replacing it with other more explicit techniques. In the present study, we measured the effects of some inclusive devices – complete pair forms and midpoint-abbreviated pair forms – on text readability (implicit and explicit) and mental representations. The results show that regardless of the inclusive device used (generic masculine, complete doublets or doublets abbreviated by the midpoint), readers quickly get used to the form. The results also reveal that texts mobilising inclusive forms generate more mental representations of women than texts written in the masculine form. We discuss these results in the light of current debates on gender-inclusive writing.